Relationship between public procurement governance and the performance of government agencies in Indonesia - Fadlila, Alise Kurniarini (Indonesian Journal of Multidisciplinary Science, 2024)
The Government Goods/Services Procurement Policy Institute (LKPP) established a policy for measuring the procurement governance index (ITKP) for Government Agencies in Indonesia as one of the tools to achieve a "Clean and Accountable Bureaucracy." This study explores the relationship and significance of ITKP indicators with government performance, as measured by the Government Agency Performance Accountability Report (AKIP). This study uses a quantitative method with secondary data obtained from LKPP and the Ministry of PANRB for the 2020-2023 period. The research sample included 72 ministries and 402 local governments. The results showed that there was a positive and significant relationship between procurement governance and the improvement of the performance of Indonesian government agencies, both in Ministry of Ministries and Agencies, Regional Governments, and the entire sample. The findings can be used as feedback and evaluation for future policy improvements, including the use of the procurement system, the qualifications and competencies of PBJ human resources, as well as the maturity level of UKPBJ.